2017
DOI: 10.1002/adma.201701019
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell and Layer‐by‐Layer Assembly of 3D DNA Crystals

Abstract: A long-standing goal of DNA nanotechnology has been to assemble 3D crystals to be used as molecular scaffolds. The DNA 13-mer, BET66, self-assembles via Crick-Watson and noncanonical base pairs to form crystals. The crystals contain solvent channels that run through them in multiple directions, allowing them to accommodate tethered guest molecules. Here, the first example of biomacromolecular core-shell crystal growth is described, by showing that these crystals can be assembled with two or more discrete layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…Further studies on these DNA crystals proved the robustness of the crystallization process, whereby introducing different defects, such as single-base mismatches, did not prevent lattice formation 103 . It was also shown that post-crystallization entrapment of the guest molecules inside the solvent channels and cavities of the crystal is possible 104 . Efforts to crystalize DNA origami unit cells have not been successful so far, although an ordered micrometer-scale 3D array of tensegrity-triangle-like DNA origami monomers was recently assembled 105 .…”
Section: Dna Crystalsmentioning
confidence: 99%
“…Further studies on these DNA crystals proved the robustness of the crystallization process, whereby introducing different defects, such as single-base mismatches, did not prevent lattice formation 103 . It was also shown that post-crystallization entrapment of the guest molecules inside the solvent channels and cavities of the crystal is possible 104 . Efforts to crystalize DNA origami unit cells have not been successful so far, although an ordered micrometer-scale 3D array of tensegrity-triangle-like DNA origami monomers was recently assembled 105 .…”
Section: Dna Crystalsmentioning
confidence: 99%
“…Recently, three-dimensional (3D) DNA crystals have been assembled into layers in the presence or in the absence of conjugated guest molecules. 31 We envision that these crystals may be suitable for this kind of structural patterning because the previous studies 32−43 on the gel-incorporation mechanism have indicated that whether or not a growing crystal incorporating surrounding gel networks can be determined by crystallization conditions including growth rate and gel strength. In principle, oscillating these crystallization conditions may result in transforming the obtained crystals between the states without (i.e., "0") and with (i.e., "1") gel incorporation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Intuitively, transforming the crystallization media containing different impurities might result in an alternate fashion. Recently, three-dimensional (3D) DNA crystals have been assembled into layers in the presence or in the absence of conjugated guest molecules . We envision that these crystals may be suitable for this kind of structural patterning because the previous studies on the gel-incorporation mechanism have indicated that whether or not a growing crystal incorporating surrounding gel networks can be determined by crystallization conditions including growth rate and gel strength.…”
Section: Introductionmentioning
confidence: 99%
“…Similar shell architectures were realized in protein crystals by glutaraldehyde cross-linking. 28 We further integrated controlled ligation and macroseeding 29 to construct yolk−shell and matryoshka-doll crystal architectures (Figures 3, C and D, S27 and S28). The critical process is to use a ligated crystal as a seed to assemble extra crystal layers and then apply controlled ligation to generate extra crystal shells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%